2019
DOI: 10.1111/acer.14076
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Evidence That Real World Sleep Timing and Duration are Associated With Laboratory‐Assessed Alcohol Response

Abstract: Background: Sleep timing and evening chronotype have been implicated in alcohol use problems but research has yet to study them in relation to theory-driven laboratory-based measures of alcohol use disorder risk. The current study examined (i) whether chronotype, sleep timing, and/or sleep duration are associated with alcohol response (subjective stimulation, sedation, and behavioral disinhibition) and (ii) if sex and race moderate these associations.Methods: Adult drinkers (N = 144; 46 female participants) co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 76 publications
(97 reference statements)
3
16
0
Order By: Relevance
“…Hasler and colleagues investigated the effect of sleep timing on response to alcohol among 148 young adults (50 were women ages 21 to 35). 58 In males (White males only) but not in females, later sleep timing and greater eveningness preference were associated with a greater selfreported stimulating effect of alcohol immediately following alcohol consumption. In addition, greater variability in sleep duration was related to greater sedation following alcohol consumption for both men and women.…”
Section: Sleep and Circadian Timingmentioning
confidence: 89%
“…Hasler and colleagues investigated the effect of sleep timing on response to alcohol among 148 young adults (50 were women ages 21 to 35). 58 In males (White males only) but not in females, later sleep timing and greater eveningness preference were associated with a greater selfreported stimulating effect of alcohol immediately following alcohol consumption. In addition, greater variability in sleep duration was related to greater sedation following alcohol consumption for both men and women.…”
Section: Sleep and Circadian Timingmentioning
confidence: 89%
“…For example, prior work indicates increased morningness (Malone et al, 2017) among Black adults, but also worse sleep among Black adolescents and young adults (Johnson et al, 2019). However, another preliminary finding suggested that Black, compared to White, drinkers were spared from an association between later sleep timing and greater stimulation in response to alcohol (Hasler et al, 2019b). Finally, understanding environmental contingencies (e.g., actual school start time) may further the understanding of mechanisms influencing this relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Studies with larger sample sizes with sufficient statistical powered to conduct whole-brain analyses are needed to investigate the reward network beyond the striatum and mPFC and other relevant networks (e.g., control and salience networks). Larger samples will also permit consideration of potential sex or race differences in associations between circadian alignment and reward function, which seem plausible based on emerging data (e.g., ( Hasler et al, 2019b ; Hasler and Pedersen, 2020 ). While the design provided temporal precedence for testing the primary aims, it remains observational and cannot speak to causal relationships between circadian alignment, reward function, and alcohol use.…”
Section: Discussionmentioning
confidence: 99%